Khlopenko M.Y., Sidorika I.M. The operability of the thrust bearing multistage centrifugal pump at unbalance of the shaft. - Хлопенко, Н.Я.; Сидорика, И.Н. (Problems of Tribology, 2014)
At shaft speeds typical of to multi-stage centrifugal pumps, arise variable efforts on pillows thrust-bearing, caused by the action of periodic forces arising at end faces beats of a mirror the crest of the shaft due to unbalance caused by the different kinds of lack of balance. This leads to violation of the hydrodynamic regime of friction and, as a consequence, to premature wear of working surfaces of friction, and in some cases to failure the bearing. To study operability thrust bearing of the multistage centrifugal pump at imbalance his shaft used previously developed by us method of calculation of dynamic loads on the pillows.Investigated the influence of axial eccentricity tolerances the crest on the operability of the oil film thrust-bearing multistage centrifugal feed pump. A specific example is shown that with unbalance of the pump rotor bearing fails due to the destruction of the oil layer at a axial eccentricity tolerances the crest.